Optimalisasi Asesmen Anekdot Untuk Penilaian Autentik Perkembangan Anak Usia Dini - Ulfa Muhrijah Harahap; Syifaushudur Harefa; Esra Theresia Sinambela; Anita Yus (Jurnal Tematik, 2026)
This study aims to optimize anecdotal assessment as a form of authentic evaluation in early childhood education. Anecdotal assessment plays a significant role in documenting children's behavior in a real, contextual, and continuous manner. This qualitative research employed a case study approach conducted at TK An-Nizam Medan, involving early childhood teachers and children aged 5–6 years. Data were collected through participatory observation, in-depth interviews, and documentation of teachers’ anecdotal notes. The findings indicate that teachers have implemented anecdotal assessment consistently to evaluate children’s development, yet several challenges remain, such as limited time, lack of standardized recording formats, and insufficient training in objective observation. Optimization strategies include developing a standardized format, providing continuous professional development for teachers, and utilizing simple digital tools to improve efficiency and data accuracy. The results show that anecdotal assessment strengthens the role of authentic assessment, helps teachers understand children’s individual needs, and enhances the overall quality of learning in early childhood education.